Morphologic Classifications and Locations of Microaneurysms and Clinical Relevance in Branch Retinal Vein Occlusion - Esaki, Yuya (Clin Ophthalmol, 2020)
PURPOSE: To classify microaneurysms (MAs) and investigate the relationships with retinal edema in eyes with branch retinal vein occlusion (BRVO). STUDY DESIGN: Retrospective, observational, consecutive case series. METHODS: Eyes with MAs due to BRVO that underwent optical coherence tomography angiography (OCTA) were enrolled. MAs on OCTA images were morphologically classified into six types: focal bulge, saccular, fusiform, mixed (saccular/fusiform), pedunculated, and irregular. The frequency, size, location, and relationships with retinal edema also were investigated. RESULTS: Twenty-four eyes of 23 patients (12 men, 11 women; mean age, 68.0 years) were enrolled. A total of 244 MAs were detected on the OCTA images. The focal bulge and saccular types accounted for over 70% of all MAs. Smaller MAs such as the focal bulge or saccular type also were detected both at the edge of the nonperfused areas (NPAs) and in collateral vessels. In contrast, larger MAs such as the pedunculated or irregular types tended to form at the edges of the NPAs. Older age, the presence of MAs in the collateral vessels, and the absence of pedunculated type were independent predictive factors for retinal edema but not the MA size, or presence in the retinal deep capillary plexus. After treatment, the mean retinal thickness decreased significantly, but the mean MA size remained unchanged. CONCLUSION: OCTA enables morphologic classification, three-dimensional analysis, and investigation of the longitudinal changes of MAs with noninvasive volumetric quantification, leading to a better understanding of the pathology of MAs in eyes with BRVO.